Implementasi Pendekatan Saintifik Dalam Pembelajaran Geografi Di Kelas X SMA Negeri 6 Sigi Kecamatan Palolo Kabupaten Sigi - Patanda, Jumelda Rura; Zumrotin' Nisa (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2023)
The study in this research raises the problem of 1) How to plan learning using a scientific approach in learning geography in class X SMA Negeri 6 Sigi, Palolo District, Sigi Regency, 2) How to implement a scientific approach in geography learning in class X SMA Negeri 6 Sigi, Palolo District, District Sigi, 3) What are the inhibiting factors for the implementation of the scientific approach in geography learning in class X SMA Negeri 6 Sigi, Palolo District, Sigi Regency. This type of research is descriptive qualitative. The targets of the research were deputy principals in curriculum areas, Geography teachers, and students of class X. Data analysis was carried out in three stages, namely: data reduction, data presentation, and drawing conclusions. The results of the research (1) The learning process with a scientific approach is in accordance with the demands of the 2013 curriculum. (2) Implementation of learning using a scientific approach. (3) The implementation inhibiting factors faced by teachers where students do not have the same ability or potential as other students in receiving learning material is a challenge for teachers to be able to properly implement the scientific approach.